2019
DOI: 10.1177/0142331219889221
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven principal component analysis-support vector machine approach for breast cancer diagnosis: Comparison and application

Abstract: In recent years, with the development of artificial intelligence, data-driven methodologies have been widely studied in fault diagnosis and detection, since an increasing number of complexities of modern complex systems make the mechanism model information difficult to obtain. Especially in people’s health monitoring, it is very difficult to achieve the mechanism model. The existing challenges, such as huge amount of data, high data dimension, large noise interference, and so forth, make the applications of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…, where r and g denote kernel parameter. 25 The kernel is also known as the radial basis function (RBF). � � insensitive loss function is used in the SVR.…”
Section: Decision Tree Regression (Dtr)mentioning
confidence: 99%
“…, where r and g denote kernel parameter. 25 The kernel is also known as the radial basis function (RBF). � � insensitive loss function is used in the SVR.…”
Section: Decision Tree Regression (Dtr)mentioning
confidence: 99%
“…Developing a model for breast cancer diagnosis with machine learning has been effective. For instance, several studies [16]- [19] have suggested that the use of a machine learning model for breast cancer diagnosis is encouraging. The machine-learning model achieved 97.77%.…”
Section: Introductionmentioning
confidence: 99%
“…By establishing a relationship between key and process variables within the available data, data-driven models can be used to predict critical product quality in the process industry (Chen et al, 2022). Data-driven models, such as latent variable models (LVMs) (including principal component analysis (PCA) (Liang et al, 2021) and partial least squares (PLS) (Chiplunkar and Huang, 2019), artificial neural networks (ANNs) (Kazmi et al, 2023), generative adversarial network (GAN) (Shao et al, 2023), Gaussian process regression (GPR) (Deringer et al, 2021) and support vector machines (SVMs) (Wu and Faisal, 2020)), have been widely used in various process controls. Although these methods are effective, they often treat measurement data as discrete samples and analyse them using multivariate statistical methods, which can overlook the continuous characteristics of process variables.…”
Section: Introductionmentioning
confidence: 99%